DYNAMICS OF HAEMATOLOGICAL AND FUNCTIONAL PARAMETERS OF PEKIN DUCK BLOOD DURING ADMINISTRATION OF ORGANIC SELENIUM PREPARATION - Ye. O. Anisimova; V. V. Pronin; L. V. Kletikova; N. N. Yakimenko (Ветеринария сегодня)
Age-related dynamics of hematological and functional parameters of Pekin duck blood during administration of organic selenium preparation DAFS-25k (at a 1.3 mg/kg dose) was presented. In order to study morphological parameters from the age of one day old to 120 days old blood was collected from axillary vein of birds prior to feeding each 15 days in the morning. To assess hematological parameters RBC and WBC count was performed, hemoglobin contents and hematocrit value were determined and color index of blood was calculated. The experiment demonstrated gradual increase in these parameters in the experimental and control groups. Birds from the experimental group demonstrated higher parameters than those of the control group. It was determined that hemoglobin contents was 9.86% higher in the experimental group in comparison with the control group due to selenium administration. The blood color index in this group was also higher (р ≤ 0.05). Biochemical blood analysis included the following parameters: total protein, albumin, uric acid, glucose, calcium, phosphorus, ALT and AST transaminase. The test results showed that during all age periods total protein and albumin contents in ducks of the experimental group exceeded those of the control group. The selenium-containing preparation had a positive influence on the carbohydrate metabolism ensuring high level of metabolic processes in birds, contributed to optimal calcium to phosphorus ratio which positively influenced mineral metabolism and development of the locomotor system. Obtained AST and ALT values in both groups are not beyond reference values which indirectly confirms absence of toxic effect on ducks’ organism if selenium is administered at the specified doses. It was determined that DAFS-25k has not affected hematological and functional parameters of Pekin duck blood and it contributed to mineral metabolism correction, reduction of stress factor effect within critical periods of development and improvement of the excretory system function.